The role of social media in learning among male students in secondary school: A case of Iraq - Abdulwaheed, Mustafa Sabah (2016)
The use of social media is a growing phenomenon which is becoming increasingly important in both private lives and the academic world. Social media are used as tools to enable users to have social interaction. The use of social media complements and enhances teaching in traditional classrooms. For example, YouTube, Facebook and Twitter provide a huge amount of material on a wide range of subjects. This study examined three possible explanations based on the Media Ecology Theory: – first, male student perceptions of social media that can contribute to the learning process; second, social media can influence male student behaviour in the learning process; and third, male students’ experiences of the social media could help to enhance the learning process. In order to achieve the objectives of this research a survey was conducted among Iraqi male students at different secondary schools in the area of Third Baghdad Al-Rasafa. The survey asked the students how social media in the classroom have changed their perceptions, experiences and behaviours in the classroom. It also explored the social media tools that might have an influence on teaching and learning styles. The type of data collected was quantitative. This study would motivate the use of social media that may contribute to enhance the learning process in secondary schools in Iraq. The analysis and interpretation of the study may be used for the improvement of the learning policies by using social media. The findings of this study showed that male students had benefited from the use of social media in the classroom. The majority of the respondents concluded that social media can help them better understand their work by enhancing their perceptions, experiences and behaviours in the classroom. This would enhance the learning process in Iraq.